Blended Cements Elaborated with Kaolinitic Calcined Clays - Tironi, Alejandra (2015)
In the clinker production process, the main component of Portland cement (PC), large amount of CO2 are emitted into the atmosphere. The use of calcined kaolinitic clays as supplementary material of cement is an alternative to mitigate the environmental impact. In this paper, the influence of the replacement of PC by two calcined kaolinitic clays (15 and 30%), with high content of metakaolinite and different reactivity was studied. Calcined kaolinitic clays were characterized, the pozzolanic activity using Frattini test, the compressive strength, rate of water absorption (sorptivity), the assemblage of hydration products and the pore size distribution were determined at 28 days. The results show that the replacement of high percentage (30%) of very reactive clays improves the mechanical behavior and durable parameters compared with those obtained for plain PC.